Global Versus Local Lyapunov Approach Used in Disturbance Observer-Based Wind Turbine Control - Gauterin, Eckhard; Pöschke, Florian; Schulte, Horst (Frontiers in Control Engineering, 2023)
This contribution presents a Lyapunov-based controller and observer design method to achieve an effective design process for more dedicated closed-loop dynamics, i.e. a maximal flexibility in an observer-based controller design with a large coincidence in desired and achieved closed loop system dynamics is intended. The proposed, pragmatic approach enhances the scope for controller and observer design by using local instead of global Lyapunov functions, beneficial for systems with widely spaced pole locations. Within this contribution, the proposed design approach is applied to the complex control design task of wind turbine control. As the mechanical loads that affect the wind turbine components are very sensitive to the closed-loop system dynamic, a maximum flexibility in the control design is necessary for an appropriate wind turbine controller performance. Therefore, the implication of the local Lyapunov approach for an effective control design in the Takagi-Sugeno framework is discussed based on the sensitivity of the closed-loop pole locations and resulting mechanical loads to a variation of the design parameters. Keywords: Global and local Lyapunov approach; Takagi-Sugeno framework; model-based controller and observer design; feedforward-feedback control; linear-matrix-inequality and pole region-based controller design; wind turbine application; elaborated wind turbine simulation model; load analysis